Surgical treatment of vulvar cancer in patients with concomitant disorders - A. A. Mukhin; A. V. Vazhenin; L. F. Chernova; V. V. Saevets; I. G. Shimotkina (Опухоли женской репродуктивной системы)
This article discusses the possibility of radical surgical treatment of vulvar cancer depending on the presence of concomitant diseases. It covers positive and negative aspects of various surgical techniques with a reconstructive component. The issue of closing the wound defect after vulvectomy and performing reconstructive surgery has always been controversial; it reduced the number of indications for such surgeries and often caused refusal from it.